Language, nations and multilingualism : questioning the Herderian ideal - Ying-Ying, Tan; Pritipuspa, Mishra (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This edited collection explores the legacy of Herder's ideas about the relationship between language and nationalism in the post-colonial world. How do anti-colonial and post-colonial nations reconcile their myriad multilingualisms with the Herderian model of one language-one nation. The model is both attractive and problematic for such nations. Why then, does the Herderian model have such valency? How has the Herderian ideal of one nation one language continued to survive beneath the uncomfortable resolution struck by new multilingual nations as they create fictions of a singular national mother tongue? To what extent is Herder still relevant in our contemporary world? How have different nations negotiated the Herderian ideal in different ways? What does the way in which multilingual postcolonial nations deal with this crisis tell us about a possible alternative framework for understanding the relationship between language and nation? By approaching this investigation from diverse archives across Asia, Africa, Europe, Latin America and the Caribbean, this volume will be able to propose answers to the above questions from a global perspective that takes into account the specificities of a range of colonial experiences and political regimes. And by extending the discussion backwards in time, a more historical reading of the making of modern nations can allow us to see how multilingualism has always disrupted constructions of monoglot nations"--
Questioning the Herderian Ideal / Pritipuspa Mishra and Ying-Ying Tan -- Herder: Blessing or Curse for Linguistic Justice? A contemporary assessment / Helder de Schutter -- Rethinking the Principle of Linguistic Homogeneity in the Age of Superdiversity / Stephen May -- From Cultural Difference to Monoglossia: Herder's Language Trap / Tony Crowley -- Multilingualism in the United States: The Long History of Official Translations / Rosina Lozano -- A noble dream?: Hindustani and Indian Nationalism in the early twentieth century / Pritipuspa Mishra -- No Laughing Matter: Learning to Speak the "Common Language" in 1950s China / Janet Y. Chen -- Nationalism, multilingualism, and language planning in postcolonial Africa / Nkonko Kamwangamalu -- Language and National Consciousness in the Postcolonial Caribbean / Andrew Daily -- The Myth of Multilingualism in Singapore Ying-Ying Tan.
OCLC-licensed vendor bibliographic record.
Keywords: Herder, Johann Gottfried, -- 1744-1803.; Language and languages -- Political aspects; Language planning -- History; Language policy -- History; Language and culture; Multilingualism; Nationalism; LANGUAGE ARTS & DISCIPLINES / General